Campur Kode dalam Acara Ini Talk Show Bulan Januari 2020 - Tiwi Armila; Inawati Inawati; Awalludin Awalludin (Jurnal Lentera Pedagogi, 2021)
This study aims to describe the form of code mixing in the Ini Talk Show on January 2020. The method used in this study is a descriptive method. Data collection techniques used are note-taking techniques and documentation techniques. The data were analyzed using descriptive analysis techniques. The results showed that the form of code mixing contained in the Ini Talk Show was in the form of words and phrases derived from local languages, slang, and foreign languages ​​such as English. In more detail, the results found are code mixing originating from regional languages ​​amounting to 21, code mixing originating from slang amounting to 93, and code mixing originating from foreign languages, namely English totaling 8. The total number of code mixing found is 122 code-mixing. Factors that cause code-mixing include social status, education, and class of language speakers, as well as many other factors that make people do code-mixing. Thus, the researcher concludes that there is a use of code mixing carried out by the speakers of the Ini Talk Show on January 2020.